Platelet aggregability and anticoagulant proteins activity during dobutamine stress echocardiography in asymptomatic patients four months after percutaneous coronary intervention - Jović, Zoran; Subota, Vesna; Džudović, Boris; Mladenović, Zorica; Marić Kocijančić, Jelena; Djurić, Predrag; Spasić, Marijan; Djenić, Nemanja; Romanović, Radoslav; Miloradović, Vladimir; Matunović, Radomir; Obradović, Slobodan (Vojnosanitetski pregled, 2021)
Background/Aim. Platelets aggregability (PA) and the activation of hemostasis during myocardial ischemia within physical or mental stress, can be one of many factors that influence the process of stent thrombosis after the percutaneous coronary intervention (PCI). The aim of the study is to investigate the relationship between the PA and activity of anticoagulant proteins with myocardial ischemia during the dobutamine stress echocardiography (DSE) in the asymptomatic patients 4 months after the PCI. Methods. The study population included 74 asymptomatic patients who had a successful PCI 4 months before a high-dose DSE. PA on epinephrine (EPI) and adenosine diphosphate (ADP) were determined by the Light Transmission Aggregometry (LTA), together with plasma activity of protein C and antithrombin before the DSE and at the peak stage of the stress test. The patients were divided into several groups on the basis of whether they have baseline or induced disturbance of segmental myocardial kinetics or not. All patients were on the clopidogrel and aspirin therapy at the time of DSE. Results. There were no statistically significant difference in the PA ADP (47.50% vs 50.20%; p = 0.970) as well as on EPI (59.30% vs 60.30%, p = 0.600) before and at the peak of DSE. A statistically significant difference was found in the anticoagulant activity of the antithrombin (84.85% vs 74.75%, p = 0.001) and protein C (77.75% vs 67.60%, p < 0.001). A significance of differences in antithrombin and the protein C, refered to the result before and at the peak levels of the test. There was no significant difference in the PA and plasma activity of anticoagulant proteins in the patients with or without induced myocardial ischemia at the peak of DSE. The patients who had an increased wall motion score index at the peak of DSE, had a higher EPI induced PA than the patients with normal myocardial contractility (68.60% vs 54.70%, respectively; p = 0.017). Conclusion. There are no changes in the PA before and after DSE, however, plasma activity of anticoagulant proteins decreased at the peak level of the test. The PA on EPI significantly increases at the peak of DSE in the patients with segmental myocardial hypocontractility.